Hard and soft computing for artificial intelligence, multimedia and security - Kobayashi, Shin-ya; Piegat, Andrzej, 1947-; Pejaś, Jerzy, 1954-; Fray, Imed El; Kacprzyk, Janusz (Advances in intelligent systems and computing ;, 2017)
This book gathers the proceedings of the 20th International Conference on Advanced Computer Systems 2016, held in Międzyzdroje (Poland) on October 19-21, 2016. Addressing topics that include artificial intelligence (AI), software technologies, multimedia systems, IT security and design of information systems, the main purpose of the conference and the book is to create an opportunity to exchange significant insights on this area between science and business. In particular, this expertise concerns the use of hard and soft computational methods for artificial intelligence, image and data processing, and finally, the design of information and security systems. The book contains a collection of carefully selected, peer-reviewed papers, combining high-quality original unpublished research, case studies, and implementation experiences.